Greek political oratory / A N W Saunders (Middlesex, 1979)
Athenian political orators would probably have made better barristers than M.P.s. Their speeches were usually forensic rather than deliberative, finely honed rather than vaguely general. Admittedly, Demosthenes' great patriotic speeches were often delivered at a constituent assembly; and Pericles Funeral Speech , as recorded by Thucydides, is both a speech of display and an acknowledged masterpiece3 of literature. But most Greek oratory resembles Lycia's speech against Eratosthenes and Androcides' self-defenses- speeches delivered in law-courts where orators used their rhetorical skills to secure a specific verdict.
Keywords: Oratory